Ecopsychosocial Aspects of Human-Tiger Conflict: An Ethnographic Study of Tiger Widows of Sundarban Delta, India - Arabinda N. Chowdhurym; Ranajit Mondal; Arabinda Brahma; Mrinal K. Biswas (SAGE Publishing, 2016)
Aims Human-tiger conflict (HTC) is a serious public health issue in Sundarban Reserve Forest, India. HTC is a continued concern for the significant mortality and morbidity of both human and tiger population. This is the first comprehensive report on Sundarban tiger-human conflicts and its impact on widows whose husbands were killed by tigers. The study attempts to explore the situation analysis of HTC and the aftermath of the incident including bereavement and coping, the cultural stigma related to being killed by a tiger and the consequent discrimination, deprivation, and social rejection, and the impact on the mental health of the tiger-widows. Methods This is a three-phase ethnographic research with a mix of quantitative and qualitative methods. In the first phase, a door-to-door village survey (3,084 households) was carried out in two villages of Sundarban, which are adjacent to the Reserve Forest, in which the incidents of human-animal conflicts and the 65 tiger-widows identified were documented. In the second phase, the 65 tiger-widows were studied to explore the ecodemography of tiger attacks and tiger-widows alongside the stigma issue by using a stigma questionnaire ( n = 49). The stigma burden was compared with normal widows ( n = 21) and snake-bite widows ( n = 18). In the third phase, the psychosocial and cultural dimensions related to tiger attacks were studied by using in-depth interviews (IDI) of the tiger-widows, focus-group discussions (FGD), and participatory mapping in the community. Clinical examinations of the mental health of the widows were also carried out in this phase. Results The mean age of the 65 widows was 43.49 ± 9.58 years. Of this, 12.3% of the widows had remarried and only 4.6% of the widows were literate. In all, 67.2% of all tiger attacks occurred as a result of illegal forest entry. The main livelihood of the former husbands of the widows were 43.8% wood cutting, 28.1% fishing, 10.9% crab catching, 9.4% tiger prawn seed (juvenile prawn), and 4.7% honey collection. The maximum number of attacks took place in the months of December (24.6%) and November (13.9%). The majority of incidences happened during the morning hours (47.7%) of the day. Of the cases, 86.1% were attacked while the person was engaged in livelihood activity. In all, 57.4% widows are recorded as living "below the poverty line". Currently, 45.5% widows earn their living by laboring work followed by forest-based livelihood activities (30%) and begging (5.2%). Tiger-widows differed significantly ( P < 0.001) from both normal and snake-bite widows on all stigma cluster scores and the total score. Of the tiger-widows, 44% were shown to be suffering from some designated mental illness. IDIs and FGDs helped to unfold the cultural construct of stigma related to tiger-killing. This can be seen in how the tiger-widows' quality of life has been negatively impacted in the way their economic and social security, health, remarriage opportunities, and child upbringing is restricted, along with a multitude of posttrauma psychological scars, deprivation, abuse, and exploitation. Conclusions The study highlights the multitude of sufferings experienced by the tiger-widows including the issues of the gender aspect of HTC and the ecopsychiatric risk factors of tiger attacks combined with the background of local sociocultural beliefs and practices. It is well known that a similar problem also exists in Bangladesh Sundarban as well, in which case it may be that a strong and practical administrative strategy for sustainable alternative income generation and a balanced conservation policy with integrated participatory forest management may go to save both human and tiger. A community ecocultural mental health program involving all the stakeholders (community, gram panchayat, and forest department) and aiming to address and even eradicate the cultural stigma of tiger attack may help to reduce the stigma burden and socicultural discrimination currently experienced by the tiger-widows.